"I Know I'm Generalizing but…": How Teachers' Perceptions Influence ESL Learner Placement. Issue 4 (31st July 2014) - Riley, Tasha
Abstract : This qualitative study focuses on the potential influence students' English as a second language (ESL) status has on teachers' placement decisions. Specifically, the study examines 21 teachers' responses to and decisions regarding fictional student record cards. Findings reveal that some teachers' placement decisions were influenced by factors beyond a student's academic achievement, such as a student's ethnicity or ESL status. This study demonstrates that even when teachers are asked to base their recommendations only on academic achievement, some teachers still attend to arbitrary factors such as a learner's group membership. Teacher educators may use these findings to sensitize teacher candidates to the implications of their unchecked stereotypes and biases.